Margarine - Kusartuti Imam Subagyo (Jurnal Kimia dan Kemasan, 1976)
Margarine like butter, is an ernulsion consisting of an internal aqueus phase enclosed in an external phase of plastic fat.The esential, materials for margarine manufacture are milk, Salt emulsifier and a suitable fat.Margarine was invented by French chemist Mege Mauries, who in 1870 received a prize offered by Louis Napoleon for a satisfactory butter substitute.Process· manufacture of margarine is described briefly.